Diagnostic potential of endoscopic ultrasonography‐elastography for gastric submucosal tumors: A pilot study. Issue 2 (10th December 2015) - Tsuji, Yuichiro; Kusano, Chika; Gotoda, Takuji; Itokawa, Fumihide; Fukuzawa, Masakatsu; Sofuni, Atsushi; Matsubayashi, Jun; Nagao, Toshitaka; Itoi, Takao; Moriyasu, Fuminori
Abstract : Background and Aim: Qualitative diagnosis for gastric submucosal tumors (SMT) is not easy. Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) in combination with EUS‐elastography (EUS‐EG) is reported useful for qualitatively diagnosing pancreatic tissues. We prospectively studied whether EUS‐EG could be useful in qualitative diagnosis of gastric SMT. Methods: We prospectively registered 25 consecutive patients with gastric SMT diagnosed by esophagogastroduodenoscopy and carried out qualitative evaluations using EUS‐EG (May 2013 to March 2015) followed by histopathological diagnosis using EUS‐FNA or endoscopic mucosal cutting biopsy. Elastic scores of gastric SMT were compared to the cytological diagnosis. Results: Of 25 patients, 22 had a confirmed cytological diagnosis. Regarding the Giovannini elastic score, of three patients with aberrant pancreas, one was score 1 and two were score 2; of eight patients with leiomyoma, seven were score 2 and one was score 3. Both of two patients with schwannoma were score 4. Of nine patients with gastrointestinal stromal tumor, six were score 4 and three were score 5. Gastrointestinal stromal tumor (GIST) is harder than other types of gastric SMT, and our study's findings suggested the usefulness of EUS‐EG, which can also assess tumor hardness of gastric SMT. Conclusion: EUS‐EG might be helpful for the differential diagnosis of gastric SMT, especially to differentiate GIST from other SMT.